2015
DOI: 10.1111/pcn.12308
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic effect of Avonex, Rebif and Betaferon on quality of life in multiple sclerosis

Abstract: Aims:The aim of this study was to evaluate the effect of various disease-modifying therapies (DMT) on quality of life in multiple sclerosis (MS).Methods: This was a three-arm parallel study with balanced randomization in which 90 newly diagnosed, definite MS subjects referred to Ghaem Medical Center, Mashhad, Iran were enrolled between 2006 and 2009. Patients were randomly allocated into three DMT groups: Avonex, Rebif and Betaferon. Health-related quality of life was assessed in MS patients at baseline and 12… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 37 publications
2
16
0
Order By: Relevance
“…A pairwise significance test was not performed. Patients in the study by Mokhber et al 186,187 in both treatment groups also showed a decrease in EDSS score, but in the opposite direction (44 µg: -1.0, p = 0.001; 250 µg: -0.6, p = 0.028). Again, a pairwise significance test was not performed.…”
Section: Disability Progressionmentioning
confidence: 84%
See 4 more Smart Citations
“…A pairwise significance test was not performed. Patients in the study by Mokhber et al 186,187 in both treatment groups also showed a decrease in EDSS score, but in the opposite direction (44 µg: -1.0, p = 0.001; 250 µg: -0.6, p = 0.028). Again, a pairwise significance test was not performed.…”
Section: Disability Progressionmentioning
confidence: 84%
“…[174][175][186][187][188][189][190][191][192][195][196][197][198][199][200]213,216,[219][220][222][223][224] Studies that reported methods of allocation concealment (the concealment of study allocation before the beginning of assigned treatment) were also judged to be at low risk of bias (n = 22/35), 171,[174][175]181,[188][189][190][191][195][196][198][199]207,213,[216][217][219][220][221][222][223][224] with the exception of one study that used open allocation. 170 All studies citing central allocation were judged as having a low risk of bias.…”
Section: Risk In Randomisation or Allocation Methodsmentioning
confidence: 99%
See 3 more Smart Citations